ОЦІНКА СОРТІВ ПРОСА ПРУТОПОДІБНОГО ЗА ВРОЖАЙНІСТЮ БІОМАСИ - Rozhko, I.; Kulyk, M. (Scientific Progress & Innovations, 2022)
Today, scientists are forced to pay more and more attention to alternative energy sources. Reducing energy dependence and sustainable development of bioenergy in Ukraine is an urgent issue. With the presence of significant areas of marginal land, proven cultivation technologies, and varieties of energy crops, it is possible to achieve the outlined goals. In addition, the formation of biomass yield and the potential of introduced switchgrass varieties have not been sufficiently studied. This article is an attempt to solve this problem based on many years of research on eleven foreign varieties of switchgrass. The research aimed to single out the best varieties of switchgrass based on economic and valuable characteristics as source material for breeding for productivity. The research methodology met the requirements of research in agronomy. General scientific, special methods of conducting the experiment, and scientific recommendations were applied. One-factor dispersion and correlation analyzes were used to interpret the obtained data. The results of the research made it possible to single out the varieties of switchgrass, which have the greatest value in terms of quantitative indicators (height and stem density). Compared to the standard variety (Cave-in-Rock), the tallest plants are formed in the Kanlow variety with the dynamics of increasing this indicator over the growing years of 256.7–298.9 cm, on average – 275.8 cm. The average value of this indicator has the following varieties: Pathfinder (241.4 cm), Shelter (240.8 cm); Cartridge, and Sunburst are almost at the same level. Dakota variety had the lowest stem height (160.4 cm). According to stem density, varieties of rod-like millet Pathfinder (539.2 pcs/m2), Blackwell (514.4 pcs/m2) and Shelter (513.7 pcs/m2) were distinguished, at the standard level – Kartraj variety (506.9 pcs/m2). This indicator was the lowest in the Nebraska variety (459.1 pcs/m2). The highest yield of above-ground green mass, which was at the standard level, was provided by the Pathfinder and Kartrage varieties of switchgrass – 24.2 and 23.6 t/ha. A significant relationship between stem density and biomass yield was established for all studied varieties of switchgrass. A close correlation between stem height and biomass yield was found for the varieties Cartrage, Blackwell, Pathfinder, Shelter, Sunburst, Kanlow, and Alamo. The unequivocal influence of both of these indicators on yield was established for the varieties Cartrage, Blackwell, Pathfinder, Shelter, Sunburst, Kanlow, and Alamo. So, Pathfinder and Shelter were singled out among the foreign varieties of switchgrass based on a complex of economic and valuable traits, which are the valuable raw material for selection for productivity.